Base Flow and Drag Characteristics of a Supersonic Vehicle with Cold and Hot Jet Flows of Nozzles - Yongchan Kim; Junyeop Nam; Tae-Seong Roh; Hyoung Jin Lee (Aerospace, 2023)
Base drag has a significant effect on the overall drag of a projectile in a supersonic flow. Herein, the base drag and flow characteristics of cold and hot gas flow in a supersonic flow are analyzed via numerical simulations. The hot gas flow is simulated using a chemical equilibrium application code based on hydrogen combustion. Two types of nozzle configurations, namely conical and contoured, are chosen for the simulation. The simulation results reveal that the change in base drag is 5–85% according to the injection gases. In the over-expanded and slightly under-expanded conditions, the base drag decreases in the hot gas flow, owing to the weak expansion fan caused by the high-temperature nozzle flow expansion, whereas in the highly under-expanded condition, the base drag decreases, owing to the strong shock wave near the base caused by the deflection of the recirculation region toward the body wall. In addition, the variations in base flow structures are observed differently compared with the cold flow; for example, a weak oblique shock wave at the nozzle exit, an increase in the distance between the shock wave and base, and deflection of the recirculation region based on the body wall are observed.